Startup acquisitions, relocation, and employee entrepreneurship - Kim, J. Daniel (Strategic Management Journal, 2022)
Abstract Research Summary This study examines the impact of startup acquisition on the acquired employees' propensity for entrepreneurship. As a new owner, the acquirer may not prioritize acquired employees' ideas to be commercialized internally, thereby increasing the odds that they are pursued externally. Leveraging employee‐employer matched data from U.S. Census on high‐tech startup acquisitions and their workforce in 1990–2011, I find that startup acquisitions substantially increase the rate of employee entrepreneurship both within and outside the target firm's industry. Post‐acquisition entrepreneurship is disproportionally concentrated among individuals with high human capital. Moreover, this effect is amplified when the target startup is relocated to the acquirer's location, and largely muted when left in its original location. Overall, this study highlights startup acquisitions as an important organizational precursor to employee entrepreneurship. Managerial Summary The past few decades have shown a significant increase in established firms acquiring startups. Although startup acquisitions can be a new source of technological innovation, talent, and market power, their long‐term outcomes likely depend on the ability to retain the acquired personnel. Using comprehensive data in the United States in 1990–2011, this study shows that startup acquisitions push many acquired employees to leave and launch their own ventures, some of which can be new competitors. This effect is disproportionately driven by the departures of founders and other top earners, who are generally the most valuable individuals to retain after the acquisition. Acquirers can mitigate these effects by allowing the acquired startup to remain in its original location rather than relocating it inside their existing establishments.